Intramyometrial Endometriotic Cyst Presenting as Dysmenorrhea and Menorrhagia - Habib, Humma; Naseer, S (Nepal Journal of Obstetrics and Gynaecology, 2013)
Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 61-62 DOI: http://dx.doi.org/10.3126/njog.v8i1.8869